Dinamika Pembangunan Masyarakat Kudus Berkonteks Sejarah Industri dan Budaya Lokal - Imaniar Purbasari (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2017)
AbstractPositive and negative aspects for developing area by the industrial sectoris the one of way to development society. Learn by trading of Kudus communitythen entered the industrial era an indicator of traditional move to moderncommunity. This research aims to explain the dynamics of developmentalcommunity from the industrial sector in Kudus. Now, Kudus community must bebrave to openness and ability to adjust the progress by the industry.Observation to get validity of data on the behavior of the people in Kudus.Development community can be seen from society to open and encouragingeach people to move utilizing natural commodities very wisely and economycommodity by the environment.Keywords: economic, social, Kudus society